Antecedents of sellers' relationship building efforts in relationship marketing: A case of the telecom sector of Pakistan - Beenish Tariq; Hayat Muhammed Awan; Suleman Ghouri (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
This research paper attempts to address the issue related to the importance and effectiveness of relationship building efforts made by a seller that are aimed at both acquiring new and retaining existing consumers. The relative importance of different kind of relationship marketing programs is analyzed to arrive at an understanding that what affects consumer's perception of a firm's relationship marketing investment the most. This research is conducted by using quantitative, structured self-administrative questionnaire through survey technique. Sample selection was based on the probability systematic sampling technique. Data has been analyzed by using AHP, correlation and SEM. AHP and regression analysis through SEM suggest that social relationship marketing programs are most valued by the consumers in highly competitive telecom sector of Pakistan. Social relationship marketing programs develop positive perception about the relationship building efforts of the sellers by increasing effectiveness of perceived relationship marketing investment. This is a cross sectional study and is confined to telecom sector of Pakistan only so it's a time bond research and the results can't be generalized to the whole service sector. This article aims to focus on the interpersonal nature of human interaction. This implies that human bonds, when created can also serve to strength the relationships between the organizations and the human customers. This also verifies the already established understanding that humans tend to capitalize on their social lives both in personal and business oriented settings. This papers aims to bridge the gap between the marketing strategies implemented and their appropriateness with the respective target customer segments. This paper also incorporates some aspects of sociology and social sciences to explain why some strategies may help marketers to get closer to consumers and are more valuable for their customers. This research is conducted in highly competitive telecom sector of Pakistan where research on the effectiveness of sellers' relationship building efforts is scarce. So this research highlights the most effective relationship marketing programs in telecom sector of Pakistan to build and maintain the relationship with the consumers. It will further guide the sellers to reduce investment on those marketing strategies which don't pay off adequate benefits.
Keywords: 330; Perceived relationship marketing investment; Social relationship marketing programs; Financial relationship marketing programs; Structural relationship marketing programs; Relationship building efforts (RBE); Analytical Hierarchy Process (AHP)